Recent Advances in Tick Antigen Discovery and Anti-Tick Vaccine Development - Abbas, Muhammad Nadeem; Jmel, Mohamed Amine; Mekki, Imen; Dijkgraaf, Ingrid; Kotsyfakis, Michail (International journal of molecular sciences, 2023)
Ticks can seriously affect human and animal health around the globe, causing significant economic losses each year. Chemical acaricides are widely used to control ticks, which negatively impact the environment and result in the emergence of acaricide-resistant tick populations. A vaccine is considered as one of the best alternative approaches to control ticks and tick-borne diseases, as it is less expensive and more effective than chemical controls. Many antigen-based vaccines have been developed as a result of current advances in transcriptomics, genomics, and proteomic techniques. A few of these (e.g., Gavac® and TickGARD®) are commercially available and are commonly used in different countries. Furthermore, a significant number of novel antigens are being investigated with the perspective of developing new anti-tick vaccines. However, more research is required to develop new and more efficient antigen-based vaccines, including on assessing the efficiency of various epitopes against different tick species to confirm their cross-reactivity and their high immunogenicity. In this review, we discuss the recent advancements in the development of antigen-based vaccines (traditional and RNA-based) and provide a brief overview of recent discoveries of novel antigens, along with their sources, characteristics, and the methods used to test their efficiency.
Keywords: Acaricides; Animals; akaricidy; vakcíny; vaccinomics; Genomics; antigen candidates; lidé; Antigens; antigeny; proteomika; tick control; Vaccines; Proteomics; klíšťata; Ticks; anti-tick vaccine; zvířata; genomika; Humans